Tari Metamorfosis Kupu-Kupu sebagai Model Pembelajaran Tari Pendidikan Dasar - Gita Kinanthi (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
The Basic Education Dance course is oriented to give an experience, theoretical and practical knowledge of creating creative dance. Characteristics of the resulting dance is the dance of elementary school age children. The purpose of this study was to describe the process of cultivating and the work of dance students of the STKIP PGRI Banjarmasin Dance Education Study Program class 2017 as a basic education dance product. This type of research is qualitative by using interview data collection techniques, observation, literature study and documentation. The results of the research obtained are that there are three stages in creating dance, consisting of exploration, improvisation and composition. The method of imitation of animals, namely the metamorphosis of butterflies, becomes the theme and basic reference in the processing of dance works. The result of the work is entitled Butterfly Metamorphosis with the storyline of the Butterfly life cycle. Although, using simple movement techniques, the dance has the potential as a learning model and teaching material for students in grades 4-6 of elementary school. Keywords: dance, butterfly metamorphosis, learning model, basic education dance.